Fuel Consumption and Air–Fuel Ratio of a Modified-Compression-Ratio Engine Using 8- and 10-Hole Injectors with E90–E100 Bioethanol Blends - M. Reza; Wawan Purwanto; Toto Sugiarto; Budi Utomo Wisesa (AEEJ : Journal of Automotive Engineering and Vocational Education, 2026)
High-bioethanol blends require appropriate fuel-injection control, particularly in engines with modified compression ratios. This study evaluated fuel consumption and air–fuel ratio (AFR) of a modified-compression-ratio spark-ignition engine using 8- and 10-hole injectors with E90, E95, and E100 blends. Experiments were conducted at engine speeds from 2000 to 8000 rpm. Fuel consumption was measured using a flow meter, while AFR was recorded during dynamometer testing. Fuel consumption increased with engine speed for both injector types. E90 produced the lowest average fuel consumption, at 1.102 L/hour for the 8-hole injector and 1.209 L/hour for the 10-hole injector. Across all fuel blends, the 8-hole injector showed lower average fuel consumption, whereas the 10-hole injector showed a narrower AFR range. These findings indicate that injector-hole configuration and high-bioethanol blend composition should be considered when tuning fuel delivery in modified-compression-ratio engines.